The Effectiveness Of Noni Leaf Extract (Morinda citrifolia L.) As Antifungal Against The Growth Of Sclerotium rolfsii In Vitro - Marsha Utami; Linda Advinda; Violita Violita; Moralita Chatri (Jurnal Serambi Biologi, 2022)
Pathogens can cause disease in plants such as stem rot, wilting and germination are the fungus Sclerotium rolfsii. S. rolfsii fungus control using synthetic fungicides. However, synthetic fungicides can cause negative impacts such as environmental pollution. Another alternative can be used is a plant-based fungicide. Plants can be used as vegetable fungicides, namely noni leaves (Morinda citrifolia L.) contain several antimicrobial compounds such as flavonoids, alkaloids and steroids that can inhibit fungal growth. The purpose of this study was to test the effectiveness and antifungal activity of noni leaf extract in inhibiting the growth of S. rolfsii. This type of research is an experimental research with 5 treatments and 3 replications which will be carried out in November-December 2021 at the Research Laboratory of the Biology Department, FMIPA UNP. The treatments given were: 0% concentration (control), 10%, 20%, 30% and 40%. The antifungal activity was analyzed descriptively. The results showed that noni leaf extract was effective in inhibiting the growth of the fungus S. rolfsii and all treatments were significantly different from the control. The antifungal activity of noni leaf extract against S. rolfsii at concentrations of 10%, 20% and 30% was weak, while the concentration of 40% was moderate.